Multidisciplinary team perceptions of the Case/Care Managers’ role implementation: a qualitative study. - De Luca, Enrico; Cosentino, Chiara; Cedretto, Stefania; Maviglia, Anna Lisa; Bucci, Janis; Dotto, Jessica; Artioli, Giovanna; Bonacaro, Antonio (Acta Biomedica Atenei Parmensis, 2022)
Background and aim of the work. The roles of Case Managers, Care Managers and fledgling Case / Care Managers integrate clinical systems to achieve optimal patient outcomes through the coordinated use of the most appropriate clinical resources. Although the Case and Care Managers roles have been researched, there is still little evidence of the development of the Case / Care Manager in the Italian Healthcare System. Aim of this research is to investigate the perception of healthcare professionals of the implementation of the Case / Care Manager figure and how it operates . Research design and methods. The study adopted a qualitative descriptive methodology with a phenomenological approach, using in-depth interviews. Participants (N = 21) were health professionals of multidisciplinary teams from several healthcare contexts in northern and central Italy, in which was activated a Case, Care, or Case / Care Manager role. The study was conducted in December 2020/ January 2021. Results. The themes showed a vision of the Case Manager, even a critical one, as a figure in transformation precisely from Case Management to Case / Care management. The themes underline how the Case / Care Manager represent a facilitator of clinical-therapeutic paths while acting as a reference figure, supporting the patient, his/her family and the multidisciplinary team. Conclusions. The results of the study confirm the Case / Care Manager as the health professional who deals with care pathways through an integrated, interdisciplinary and personalized approach, placing the person at the centre and thus overcoming a disease-centered approach.